Answer:
![(x+1-i)(x+1+i)](https://tex.z-dn.net/?f=%28x%2B1-i%29%28x%2B1%2Bi%29)
Step-by-step explanation:
![(x+1-i)(x+1+i)\\\\=(x+1)^2 -i^2~~~~~~~~~~~~~;[a^2 -b^2 = (a+b)(a-b)]\\\\=x^2 +2x +1 -(-1)\\\\=x^2 +2x +1+1\\\\=x^2 +2x +2](https://tex.z-dn.net/?f=%28x%2B1-i%29%28x%2B1%2Bi%29%5C%5C%5C%5C%3D%28x%2B1%29%5E2%20-i%5E2~~~~~~~~~~~~~%3B%5Ba%5E2%20-b%5E2%20%3D%20%28a%2Bb%29%28a-b%29%5D%5C%5C%5C%5C%3Dx%5E2%20%2B2x%20%2B1%20-%28-1%29%5C%5C%5C%5C%3Dx%5E2%20%2B2x%20%2B1%2B1%5C%5C%5C%5C%3Dx%5E2%20%2B2x%20%2B2)
Step-by-step explanation:
Answer:N
Step-by-step explanation:
Answer:
1/4
Step-by-step explanation:
The inverse function tells you the input value that corresponds to the given output value of the function.
<h3>Application</h3>
You want f^-1(3), which is the value of x such that f(x) = 3.
f(x) = 3 = 4x +2
1 = 4x . . . . . . subtract 2
1/4 = x . . . . . divide by 4
The inverse function of 3 is 1/4:
![\boxed{f^{-1}(3)=\dfrac{1}{4}}](https://tex.z-dn.net/?f=%5Cboxed%7Bf%5E%7B-1%7D%283%29%3D%5Cdfrac%7B1%7D%7B4%7D%7D)
Answer:
670
Step-by-step explanation:
(3*1+2)+(3*2+2)+........(3*20+2)=670